Emerging technologies of augmented reality : interfaces and design - Haller, Michael, 1974- .; Billinghurst, Mark, 1967- .; Thomas, Bruce (Idea Group Pub., 2007)
"This book provides a good grounding of the main concepts and terminology for Augmented Reality (AR), with an emphasis on practical AR techniques (from tracking-algorithms to design principles for AR interfaces). The targeted audience is computer-literate readers who wish to gain an initial understanding of this exciting and emerging technology"--Provided by publisher.